Legal review of the liability of the Bissmika Usaha Nusantara savings and loan cooperative for unlawful acts against customers - Halizah Destriana; Asnawi Asnawi; Faturohman Faturohman (Journal of Law Science, 2024)
This study examines the legal review of the liability of the Bissmika Usaha Nusantara Savings and Loan Cooperative for unlawful acts committed against its customers. As a financial institution operating under the cooperative model, the cooperative is bound by legal obligations to uphold the principles of trust, transparency, and accountability. However, issues arise when the cooperative engages in actions that potentially harm customers, such as mismanagement of funds, lack of clarity in contracts, or failure to comply with statutory regulations. This research adopts a normative juridical approach, analyzing laws and regulations governing cooperatives in Indonesia, particularly those relating to cooperative responsibility, contractual obligations, and unlawful acts (perbuatan melawan hukum). The findings indicate that cooperatives can be held liable both institutionally and personally through their management, depending on the nature of the violation. Furthermore, legal remedies available to customers include civil claims for damages, dispute resolution through cooperative forums, and escalation to the judiciary. The study contributes to understanding cooperative accountability and strengthening consumer protection within Indonesia’s cooperative financial system. This study aims to analyze the legal responsibility of the Bissmika Usaha Nusantara Savings and Loans Cooperative for unlawful acts that harm customers and examine the dispute resolution mechanisms that can be taken.